Key factors in the contingency plan for COVID-19 during the Magal celebration in 2020 - Diouf, M; Gueye, L; Ndiaye, L (Public Health, 2021)
No abstract
Public Health. 2021 Sep; 198: e1–e2. Published online 2021 Apr 8. doi: 10.1016/j.puhe.2021.03.009
Keywords: K. Ngom; A. Mbacké; A. Sarré; Université Cheikh Anta Diop; Sénégal; CEA-AGIR